LEGAL CERTAINTY FOR LAND DISPUTE SETTLEMENT IN REGULATION OF THE MINISTER OF AGRARIA NUMBER 21 OF 2020 REGARDING HANDLING AND SETTLEMENT OF LAND CASES - Muhamad Irayadi (International Peneliti Ekonomi, Sosial dan Teknologi, 2023)
Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21 of 2020 concerning Settlement of Land Cases in which dispute resolution through the BPN aims to provide justice and legal certainty to the community regarding land tenure, ownership, use and utilization. In this study, the author uses normative/juridical legal research methods and the results of the discussion of the agrarian dispute resolution mechanism can be carried out by resolving disputes through the Courts and dispute resolution outside the court and handling cases carried out by the Ministry of ATRBPN as stated in CHAPTER IV PermenATR/Ka.BPN Number 21 of 2020 concerning Handling and Settlement of Land Cases.